2016
DOI: 10.1002/adsc.201500390
|View full text |Cite
|
Sign up to set email alerts
|

Organohalogenite‐Catalyzed Spiroketalization: Enantioselective Synthesis of Bisbenzannulated Spiroketal Cores

Abstract: An ew core structure-motivated strategy for the intramolecular aromatic spiroketalization process wasf ound and used for the enantioselective synthesis of bisbenzannulated spiroketals,t he bioactive core of rubromycins,w ith high levels of enantioselectivity (up to 98% ee) via an organohalogenite-mediated asymmetric intramolecular aromatic spiroketalization. This is the first organocatalytic method for the construction of opticallyp ure bisbenzannulated spiroketals.Keywords: asymmetric synthesis; organocatalys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 80 publications
(9 reference statements)
0
3
0
Order By: Relevance
“…As far as we are aware, dimer 3 is new and might be an interesting structure for benzofuran based pharmaceuticals . A search using the structures of products 4 a , 4 b , 5 , 5 a , 6 , 6 a , 6 b and 7 indicated that these compounds have also not been previously characterized although some bioactive compounds such as Arundinone B, or the drug Griseofulvin (Figure ) contain the core structure of compound 4 a .…”
Section: Resultsmentioning
confidence: 99%
“…As far as we are aware, dimer 3 is new and might be an interesting structure for benzofuran based pharmaceuticals . A search using the structures of products 4 a , 4 b , 5 , 5 a , 6 , 6 a , 6 b and 7 indicated that these compounds have also not been previously characterized although some bioactive compounds such as Arundinone B, or the drug Griseofulvin (Figure ) contain the core structure of compound 4 a .…”
Section: Resultsmentioning
confidence: 99%
“…The design and synthesis of biologically active spiro-heterocycles have attracted the attention of many pharmacologists and chemists [14,15]. In particular, the spiro-heterocycles that contain benzofuran have become one of the most interesting classes of molecules due to their notable biological activities [ [16][17][18]. For example, griseofulvin A is one of the earliest spirocyclic drugs to exhibit antifungal activity [19], while spiro-benzofuran B, with isobenzofuranone and benzofuranone motifs, has been found to be a core chemical skeleton for antivirals against influenza viruses [20].…”
Section: Introductionmentioning
confidence: 99%
“…Despite these advances, the development of more atom- and step-economic methods starting from easily available substrates under mild conditions is still highly desirable for the synthesis of benzannulated [6,6]-spiroketals. Our group has a longstanding interest in this field and has developed a series of efficient methods for the syntheses of benzannulated [5,6]-spiroketals . In accordance with our interest in developing synthetic tools for the synthesis of natural products containing benzannulated [6,6]-spiroketal motifs, we wish to develop a new and efficient method for the stereocontrolled synthesis of this skeleton.…”
mentioning
confidence: 99%